A Flexible Conformal Phased Array With Embedded Magnetic Particles Based Composite Right/Left Handed Metamaterial Phase Shifters - Muhammad Ayaz; Irfan Ullah; Adnan Iftikhar; Syed Muzahir Abbas; Benjamin D. Braaten; Shahid Khattak; Moath Alathbah (IEEE Access)
In this study, a flexible and fully printable four element patch antenna array bent on a cylindrical-shaped surface for main beam steering is proposed. The individual phases of the microstrip patches in the array are varied by using novel planar phase shifters constituted of microstrip composite right/left-handed (CRLH) lines ingrained with microparticles. The reinforcement of newly introduced microparticles in the CRLH transmission line structure makes it a variable phase shifter, which is fabricated on a flexible substrate in completely planar and conformal configurations. The magnetic particles-based CRLH-TL phase shifter (MP-CRLH) consists of multiple cavities in the substrate filled with micron-sized silver-coated ferrite particles. These particles in the cavity are magnetically aligned by a small magnet placed beneath the cavity. A particular phase shift can be achieved by activating particles in multiple cavities in the MP-CLRH phase shifter. The optimum locations of the cavities partially filled with magnetic particles for a particular phase shift have been explored after extensive 3D simulations in the frequency domain using CST Studio Suite. The main advantage of using the MP-CRLH phase shifter is that it can be conformed to non-planar surfaces, such as cylindrical-shaped in this scenario. As compared to conventional IC/discrete components-based phase shifters, the working of the novel MP-CRLH phase shifter is independent of external SMT and lumped circuit components for its biasing. The four unit-cell cascaded MP-CRLH phase shifter is then integrated with a four-element patch array on a cylindrical-shaped surface with radii of 30 cm and 10 cm. The main pattern of the array has been successfully scanned at 0°, −15°, and +30° using the integrated MP-CRLH phase shifter at.2.45 GHz. The full-wave simulation results are validated with the measured radiation patterns in a fully anechoic chamber facility. The conformal phased array integrated with MP-CRLH phase shifters on a flexible substrate can be used for applications like on-body communication systems, wearable devices, flexible electronics, and aircraft communication systems.